Cerebellar Gray Matter Volume in Tinnitus - Mennink, Lilian M.; Koops, Elouise A.; Langers, Dave R. M.; Aalbers, Marlien W.; van Dijk, J. Marc C.; van Dijk, Pim (Frontiers in Neuroscience, 2022)
Tinnitus is the perception of sound without an external source. The flocculus (FL) and paraflocculus (PFL), which are small lobules of the cerebellum, have recently been implicated in its pathophysiology. In a previous study, the volume of the (P)FL-complex correlated with tinnitus severity in patients that had undergone cerebellopontine angle (CPA) tumor removal. In this study, the relation between tinnitus and grey matter volume (GMV) of the (P)FL-complex, GMV of the other cerebellar lobules and GMV of the cerebellar nuclei is investigated in otherwise healthy participants. Data was processed using the SUIT toolbox, which is dedicated to analysis of imaging data of the human cerebellum. GMV of all cerebellar lobules and nuclei were similar between tinnitus and non-tinnitus participants. Moreover, no relation was present between tinnitus severity, as measured by the Tinnitus Handicap Inventory, and (P)FL-complex GMV, tonsil GMV, or total cerebellar cortical GMV. These results suggest that in otherwise healthy participants, in contrast to participants after CPA tumor removal, no relation between the GMV of neither the (P)FL-complex nor other cerebellar lobules and tinnitus presence and severity exists. These findings indicate that a relation only exists when the (P)FL-complex is damaged, for instance by a CPA tumor. Alternatively, it is possible that differences in (P)FL-complex GMVs are too small to detect with a voxel-based morphometry study. Therefore, the role of the (P)FL-complex in tinnitus remains to be further studied.